Evaluating cytotoxicity of methyl benzoate in vitro - Heeyoun Bunch; Jungeun Park; Hyeseung Choe; Md Munir Mostafiz; Jang-Eok Kim; Kyeong-Yeoll Lee (Heliyon, 2020)
Methyl benzoate (MB) is a small, hydrophobic organic compound that is isolated from the freshwater fern, Salvinia molesta. Because of its pleasant odor, it has been used as a fragrance and flavor enhancer. In addition, it is used to attract orchid bees for pollination in the farm and has been tested for its potential to be developed as a green pesticide targeting a diverse group of insects. In spite of its wide applications, the safety of MB to humans remains poorly understood. In this study, we tested the cytotoxicity of MB against cultured human cells, including kidney, colon, and neuronal cells. Furthermore, other natural and synthetic benzoic acids such as ethyl benzoate (EB) and vinyl benzoate (VB) were compared with MB for their similarity and broad commercial and industrial applications. We found that MB and VB have the least and most overall toxicity to the tested human cells, respectively. In addition, the expression of some genes involved in cell cycle, protein quality control, and neurotransmission such as cyclin D1, HSP70, and ACHE genes was differentially expressed in the presence of these chemicals, most noticeably in treatment of VB. Our study provided the LC50 values of these benzoic acids for human cells in vitro and suggested their mild toxicity that should be considered in the industrial and agricultural applications to be within safe limits.